MODEL PENGEMBANGAN PEMBELAJARAN IPS BERBASIS MULTIKULTUR DALAM RANGKA MENANAMKAN NILAI-NILAI PANCASILA - Kiki Aryaningrum (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
Social Science Learning is one of the fundamental instruments in the framework of national education as a medium for the character formation of the nation in the midst of heterogeneity or pluralism that became the main character of the Indonesian nation. Indonesian nation has a variety of differences and become a wealth of Indonesian man. Differences of ethnicity, culture, customs, religion, race, gender, social strata and political alliances are very clearly inherent in Indonesian society. This study aims to find Social Science Learning model based on multicultural learning in order to create Pancasila value to students. The method used is literature study by finding reference theory and previous research relevant to case and problem discussed in this research. The result of the research shows that the learning of IPS based on multicultural in order to create Pancasila values can be designed by using ADDIE model. Which includes: Analyze, Develop, Evaluation, and Implementation. IPS students can understand and practice the value of pluralism, democracy, humanism and justice related to the cultural differences that exist around it.